Infrared Studied of Cu-Phthalocyanine Dye - Srivastava, K.P.; Kumar, A. (Asian Journal of Chemistry, 2010)
The infrared spectra of Cu-phthalocyanine were recorded. The analysis has been carried out by assuming C4h point group symmetry. The vibrational frequencies appeared are lesser than expected.